Efficacy of Lutalyse® as an Abortifacient in Feedlot Heifers - Simms, D.; Kuhl, Gerry L.; Tonn, S.; Schalles, R. (Kansas State University. Agricultural Experiment Station, 2010)
Lutalyse aborted 86.7% of heifers 40 to 100 days pregnant. Of four heifers tested at 101 to 150 days pregnant, all aborted. Open heifers gained faster (P<.05) than heifers that either were aborted or pregnant at slaughter. Those pregnant at slaughter had lower (P<.05) dressing percentages than either open or aborted heifers.
Keywords: Beef; Lutalyse®; Heifers; Dressing percentage